(untitled) (Italian Journal of Public Health, 2006)
Healthcare delivery systems are facing fundamental challenges. New ways of organising theses systems based on the different needs of stakeholders’ are required to meet these challenges. While medicine is currently undergoing remarkable developments from its morphological and phenotype orientation to a molecular and genotype orientation, promoting the importance of prognosis and prediction, the discussion about the relevance of genome-based information and technologies for the health care system as a whole and especially for public health is still in its infancy. The following article discusses the relevance of genome-based information and technologies for individual health information management, health policy development and effective health services.